2013
DOI: 10.1645/12-80.1
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystisspp.: Frequency and Subtype Distribution in Iron Deficiency Anemic Versus Non-Anemic Subjects from Egypt

Abstract: Many helminthic and protozoal infections have been implicated in iron deficiency anemia (IDA) but few reports have suggested a link between Blastocystis sp. infection and IDA. Herein, we investigated the frequency and the association of the Blastocystis sp. genotype with IDA. Two-hundred and six stool samples were examined for Blastocystis sp. Samples were obtained from 96 cases with a confirmed diagnosis of IDA and 110 matched non-anemic controls. The prevalence of the parasite was significantly higher in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…It may colonize the bowels and is commonly isolated in individuals with neither gastrointestinal complaints nor symptoms [ 19 , 47 ]. However, Blastocystis was also identified as the only causative agent of gastrointestinal or dermatological symptoms, such as abdominal pain, diarrhea, nausea, vomiting, bloating, anorexia, or, less commonly, urticaria, intense itching [ 56 , 57 ], or iron deficiency anemia [ 96 98 ].…”
Section: The Role Of Blastocystis In the Human Gutmentioning
confidence: 99%
“…It may colonize the bowels and is commonly isolated in individuals with neither gastrointestinal complaints nor symptoms [ 19 , 47 ]. However, Blastocystis was also identified as the only causative agent of gastrointestinal or dermatological symptoms, such as abdominal pain, diarrhea, nausea, vomiting, bloating, anorexia, or, less commonly, urticaria, intense itching [ 56 , 57 ], or iron deficiency anemia [ 96 98 ].…”
Section: The Role Of Blastocystis In the Human Gutmentioning
confidence: 99%
“…ST1-9 has so far been found in humans, with a majority belonging to ST1-4 [ 16 ]. In Africa, the prevalence of Blastocystis subtypes has been studied in the northern and western parts of the continent, namely Egypt [ 17 20 ], Libya [ 16 , 21 ], Senegal [ 9 ], Liberia and Nigeria [ 16 ], while data from East Africa is sparse. A study from Petrášová et al [ 22 ] described the Blastocystis subtypes found in non-human primates, as well as in six human researchers, in Rubondo Island in the northwest part of Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…[ 39 ] Moreover, in a recent study performed in Egypt, the frequency of parasites was significantly higher in cases with IDA compared to controls. [ 46 ] Furthermore, a study conducted recently to compare hematological indices in cases with Blastocystis hominis infection against healthy controls revealed that the frequency of SI was significantly lower in cases with B. hominis infection compared to controls. [ 45 ]…”
Section: Discussionmentioning
confidence: 99%